2012
DOI: 10.1007/s10552-012-9899-8
|View full text |Cite
|
Sign up to set email alerts
|

Can pictorial warning labels on cigarette packages address smoking-related health disparities? Field experiments in Mexico to assess pictorial warning label content

Abstract: Objective This study aimed to determine the most effective content of pictorial health warning labels (HWLs) and whether educational attainment moderates these effects. Methods Field experiments were conducted with 529 adult smokers and 530 young adults (258 nonsmokers; 271 smokers), wherein participants reported responses to different HWLs printed on cigarette packages. One experiment involved manipulating textual form (testimonial narrative vs didactic) and the other involved manipulating imagery type (dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 29 publications
5
65
2
4
Order By: Relevance
“…Use of a wider range of brands for comparison is recommended for research in countries considering implementing plain packaging. Although the study employed a computer image instead of actual packs, previous packaging research demonstrates that results are generally consistent regardless of stimulus presentation modality 22 35 36. The outcome measures used in this study pose an additional limitation.…”
Section: Discussionmentioning
confidence: 93%
“…Use of a wider range of brands for comparison is recommended for research in countries considering implementing plain packaging. Although the study employed a computer image instead of actual packs, previous packaging research demonstrates that results are generally consistent regardless of stimulus presentation modality 22 35 36. The outcome measures used in this study pose an additional limitation.…”
Section: Discussionmentioning
confidence: 93%
“…In the cluster -communication‖, Thrasher et al (2012) found that the warning labels on cigarette packages worked most effectively at getting a message across. In the group called -tuxedo‖, Zacher et al (2014) also discussed the issue of information and warnings on cigarette packages.…”
Section: Figure 5 Network Between Countriesmentioning
confidence: 99%
“…Las imágenes de advertencia muestran el impacto negativo del consumo de tabaco mediante imágenes impactantes, y pretenden promover conductas de rechazo hacia el consumo (Farrelly et al, 2008). Esta estrategia ha demostrado ser efectiva para un amplio grupo de personas (Borland et al, 2009;Hammond, Reid, Driezen y Boudreau, 2013;Hammond et al, 2012;Thrasher et al, 2012), particularmente aquellas que han iniciado recientemente la conducta de fumar y aquellas que están interesadas en abandonarlo, especialmente cuando las imágenes de advertencia son muy visibles y señalan los efectos negativos del consumo de tabaco (Hammond, Fong, McNeill, Borland y Cummings, 2006). El estudio de la respuesta emocional hacia las imágenes de advertencia se ha limitado, por lo general, al uso de encuestas y grupos focales (Hammond, 2011), los resultados de estas investigaciones muestran que las imágenes son más efectivas para comunicar el mensaje de daño y peligro en comparación a cuando sólo se usa el mensaje en texto (Vardavas, Connolly, Karamanolis y Kafatos, 2009) y que los fumadores reportan algún grado de miedo, asco o ira ante las imágenes de advertencia, y que las emociones de miedo y asco se asocian a la disminución del consumo de tabaco posteriormente (Hammond, Fong, McDonald, Brown y Cameron, 2004).…”
Section: Introductionunclassified